Maintaining dual career balance: A scenario perspective on Swedish university student-athletes’ experiences and coping - Linnér, Lukas; Stambulova, Natalia; Ziegert, Kristina (Scandinavian Journal of Sport and Exercise Psychology, 2021)
A dual career (DC) scenario perspective was introduced in the Erasmus+ Sports project “Gold in education and elite sport” (GEES) and is characterized by integration of student-athletes’ athletic and non-athletic demands into difficult situations or periods (i.e., scenarios) requiring coping efforts. In this study we consider balance as the primary challenge for student-athletes and set out to identify DC scenarios that influenced university student-athletes’ optimal DC balance, and the factors involved in coping with such scenarios. We implemented a post-positivist qualitative design through semi-structured interviews with six university student-athletes. Our thematic analysis generated seven DC scenarios (e.g., A sport event coincides with exams, and Finalize degree project and continue to train and compete). The scenarios, their characteristics and student-athletes’ corresponding coping are described. Based on the findings, we suggest an updated definition of DC scenarios and present their taxonomy, with four types of DC scenarios in which student-athletes’ circumstances require (a) several shifts between sport and study in daily life, (b) prioritizing sport while maintaining study, (c) prioritizing study while maintaining sport, and (d) prioritizing personal life while maintaining sport and study. We discuss how these developments can be useful for DC research and practice.